Plant use in material culture and firewood practices: linking ethnobotany and archaeology in traditional West African villages - Tereza Majerovičová; Miguel Ballesteros; Idrissa Manka; Alexa Höhn; Jan Altman; Jaromír Beneš (Vegetation History and Archaeobotany, 2026)

Recent decades are the warmest in over 400 years in Northeast Asia: evidence from tree-ring anatomy - Nela Altmanová; Georg von Arx; Jiří Doležal; Pavel Fibich; Toshihiko Hara; Jan Altman (Climatic Change, 2026)
Recent rapid climate warming often exceeds the rate and magnitude of pre-industrial variability over the Common Era. While contemporary warming exhibits a high degree of global synchrony, pre-industrial warm and cold periods were often spatially heterogeneous and asynchronous. Consequently, reliable regional paleoclimate records remain essential for understanding past climate variability. Here, we present an annually resolved, 411-year-long reconstruction of June 9–July 30 minimum temperature based on cell wall thickness of Picea glehnii trees from Hokkaido, Japan. Our reconstruction, developed from non-detrended chronologies and daily climate data ( r = -0.68, p < 0.05), provides a spectrally unbiased record of temperature variability across Northeast Asia. It captures pronounced cold and warm periods that align with historical records and regional climate reconstructions. For instance, it reveals cold periods in the 17th century corresponding to the Maunder Minimum and a distinct cold period in the 1830s, which coincided with one of the severest famines in Japanese history. Crucially, the period from 1994 to 2016 was the longest warm period in the entire reconstruction. The reconstruction also shows significant, persistent multidecadal variability that likely reflects the Pacific Decadal Oscillation. These findings highlight the strong potential of quantitative wood anatomy to improve our understanding of long-term climate dynamics and, thus, reduce uncertainties in future climate projections.

Larix gmelinii growth limitation shifts from nitrogen availability to drought under warming and permafrost degradation - Zecheng Chen; Binqing Zhao; Wenqi Song; Hans W. Linderholm; Jan Altman; Keyu Zhang; Hanjun Dong; Xinran Huang; Haoyuan Chen; Xiaochun Wang (Global and Planetary Change, 2026)

A modular handle for increment borers: Improving versatility, efficiency, and safety in dendrochronological fieldwork - Jan Altman; Chuan-Chou Shen; Ludvig Löwemark; Hsin-Lin Wei (Dendrochronologia, 2026)

Climate and Volcanic Activity Modulate Area–Distance Effects on Plant Diversity Along the Temperate–Subarctic Island Volcanic Arc - Kirill Korznikov; Vyacheslav Barkalov; Pavel Fibich; Jan Altman; Jiří Doležal (Journal of Biogeography, 2026)
Aims To evaluate how equilibrium (ETIB) and niche‐based (NTIB) island‐biogeography frameworks jointly explain taxonomic and phylogenetic diversity in a temperate–subarctic, volcanically active archipelago. Location Kuril Islands, northwestern Pacific (44°–50° N). Time Period Present. Taxon Vascular plants. Methods We compiled island‐level floras. We quantified species richness (SR) and phylogenetic diversity metrics and related them to latitude, area, distance, a composite isolation index, elevation, volcanic bedrock cover, vegetation‐type diversity and aggregated climatic indices. Analyses combined linear and second‐order polynomial regressions, β‐diversity partitioning, non‐metric multidimensional scaling and structural equation models. Results Latitude emerged as the primary large‐scale filter shaping both SR and phylogenetic diversity. Volcanic activity and isolation further constrained floristic diversity, together generating a pronounced mid‐archipelago diversity trough. Maximal elevation was associated with higher SR but did not translate into detectable shifts in phylogenetic structure. Island area influenced diversity mainly indirectly, through its links with elevation and dispersal accessibility. Floristic differences among islands were driven predominantly by species turnover rather than nested species loss, indicating systematic replacement along the latitudinal gradient. Isolation effects were strongly non‐linear, consistent with threshold‐like limits to colonisation. Main Conclusions Area–distance relationships predicted by ETIB are strongly context‐dependent. Macroclimatic filtering and long‐term volcanic activity outweigh simple spatial predictors, while habitat heterogeneity exerts a secondary, modulatory role. Together, our results integrate ETIB and NTIB perspectives by showing how environmental filtering and niche availability interact in a volcanically active, temperate–subarctic island system.

deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

Hidden forest loss: challenges in detecting wind- and insect-driven forest disturbances with global forest change landsat-based products in mixed southern boreal forests - Kirill Korznikov; Dmitriy Kislov; Jiří Doležal; Jan Altman (Remote Sensing Applications: Society and Environment, 2025)

Unprecedented tropical cyclone in temperate‐boreal ecotone drives declines in emergent conifers and canopy complexity - Kirill Korznikov; Tatyana Petrenko; Violetta Dzizyurova; Dmitriy Kislov; Jiří Doležal; Jan Altman (Ecology, 2025)
Poleward shifts in tropical cyclone (TC) activity have introduced unprecedented disturbances to Northeast Asia's boreal and temperate‐boreal ecotone forests. As TCs migrate northward, they increasingly influence previously unaffected regions, yet their impacts on forest structure and species composition remain poorly understood. This study examines TC Maysak (2020), the most intense cyclone recorded in the ecotone forests near the Chinese–Russian border, and its effects on tree vulnerability and canopy structure. Using high‐resolution drone‐based orthophotographs, we analyzed fallen tree dimensions across four affected sites within protected forests, identifying key differences between coniferous and broadleaf species. Tall emergent conifers, including Manchurian fir ( Abies holophylla ) and Korean pine ( Pinus koraiensis ), were disproportionately susceptible to windthrow, with mean fallen heights exceeding the average canopy height by 4.88 ± 0.20 m (13.62 m maximally). In contrast, broadleaf species such as Mongolian oak ( Quercus mongolica ) exhibited minimal height variation relative to the canopy average. Our findings highlight TCs as emerging disturbance agents in Northeast Asia's temperate‐boreal ecotone, preferentially removing emergent conifers, simplifying canopy structure, and promoting broadleaf dominance. As TC activity intensifies under global climate change, these disturbances may accelerate forest transitions in climatically sensitive ecotone forests.

Enhancing tree-ring visibility: A comparative study of sample and imaging techniques for 62 temperate tree species - Nela Altmanová; Martina Hrádková; Eva Návratová; Vít Pejcha; Václav Bažant; Savannah Collins-Key; Jiří Doležal; Daniel Druckenbrod; Tsutomu Enoki; Keyan Fang; Pavel Fibich; Grant L. Harley; et al. (Dendrochronologia, 2025)

Beyond meteorological data: Modelling tree growth with ERA5-Land - Marian Schönauer; Christoph Pucher; Jan Altman; Josef Weißbacher; Lars Sprengel; Boris Rewald (Agricultural and Forest Meteorology, 2025)

Plant and saproxylic beetle dynamics during succession in lowland temperate broadleaf forests reveal only short periods of increased diversity - Vojtěch Lanta; Pavel Sebek; Petr Kozel; Jan Altman; Radek Bače; Zuzana Chlumská; Tomáš Černý; Miroslav Dvorský; David Hauck; Kirill Korznikov; Jan Miklín; Štěpán Vodka; et al. (Biological Conservation, 2025)

Growth dynamics and climate sensitivities in alpine cushion plants: insights from Silene acaulis in the Swiss Alps - Samresh Rai; Nikola Breme; Veronika Jandova; Vojtech Lanta; Jan Altman; Adam Taylor Ruka; Christian Rixen; Jiri Dolezal (Alpine Botany, 2025)
Understanding alpine plants’ growth dynamics and responses to warming is essential for predicting climate change impacts on mountain ecosystems. Here, we examine growth determinants in the alpine cushion plant Silene acaulis in the Swiss Alps, exploring ontogeny, elevation, and climate influences. We collected 40 Silene individuals and 159 individuals from 38 co-occurring alpine species across 2200–3130 m elevations in the Swiss Alps, analyzing age and growth histories through annual growth rings. While comparing growth rates, we found that Silene was relatively slow-growing. However, Silene exhibited a dual growth strategy, initially rapid and then slowing after ~ 20 years, challenging perceptions of its longevity. Similar ontogenetic trends were observed in other alpine species, albeit with variations based on species and elevation. The consistent unimodal growth-elevation pattern in Silene and other alpine plants, peaking at ~ 2400 m, underscores shared environmental constraints on alpine plant growth. Additionally, cross-dating growth ring series and correlating with daily climate data enabled the precise assessment of warming impacts on growth. Silene ’s growth is influenced by year-to-year climate variability, with warming-induced moisture stress and overheating during spring and summer adversely affecting its growth. Despite being low-statured, Silene is not completely decoupled from atmospheric influences. The heat-trapping function of Silene , effective in mature and well-formed cushions, makes it susceptible to adverse effects as temperatures rise. This sensitivity raises concerns about the potential dieback of Silene cushions, as witnessed during recent heatwaves, and emphasizes the broader ecological implications for alpine ecosystems, given Silene ’s role as a crucial nurse plant.

Spatial heterogeneity of tree-growth responses to climate across temperate forests in Northeast Asia - Nela Altmanová; Pavel Fibich; Jiří Doležal; Václav Bažant; Tomáš Černý; Julieta G. Arco Molina; Tsutomu Enoki; Toshihiko Hara; Kazuhiko Hoshizaki; Hideyuki Ida; Pavel Janda; Akira Kagawa; et al. (Agricultural and Forest Meteorology, 2025)

Changes in Distribution Ranges of Abies Species Dominating in the Forests of Northeast Asia Since the Last Glacial Maximum - Tatyana Petrenko; Violetta Dzizyurova; Jan Altman; Jiří Doležal; Dmitriy Kislov; Kirill Korznikov (Journal of Biogeography, 2025)
Aim Climate variations within the stadial–interstadial cycles drive shifts in the distribution of forest dominants. This study examines how climate dynamic alters the distribution ranges of two boreal and one cold‐temperate Abies species dominating in Northeast Asia. Location Northeast Asia: China, Japan, Korea and Russia. Taxon Abies nephrolepis , A. sachalinensis (sect. Balsamea ) and A. holophylla (sect. Pseudopicea ). Methods We developed climate envelope species distribution models (SDMs) using warmth and coldness indices, the continentality index, and proxies of rain and snow precipitation indices. We interpolated SDMs on reconstructed climates for the Last Glacial Maximum (LGM) and the Holocene Climatic Optimum (HCO) and to predicted climates for 2070 under global warming scenarios RCP2.6 and RCP8.5. Results During the LGM, the climatic optimum for all species covered extensive areas on the shelves of the Japanese and Yellow Seas, facilitated by the global sea level drop. The interglacial climatic optimum supports the expansion of A. nephrolepis and A. sachalinensis compared to the LGM, whereas the range of A . holophylla climatic niche range experiences a reduction. Main Conclusions Our findings highlight the significant impact of climatic oscillations on the spatial distribution and ecological dynamics of Abies species in Northeast Asia. The contrasting responses of boreal and temperate fir species to glacial and interglacial periods underscore the complex interplay between climate change and the distribution of forest dominants. Projections under future warming scenarios suggest that Abies species will face further range shifts, emphasising the need for adaptive forest management and conservation strategies, especially in the southern part of their distribution.

Climate drivers of Pinus ponderosa tree development on volcanic tephra deposits in the Southwestern USA: Insights from radial increment and wood density variations - Julieta Gabriela Arco Molina; Jan Altman; Samresh Rai; Kirill Korznikov; Vit Pejcha; Miroslav Dvorsky; Jiri Doležal (Dendrochronologia, 2024)

Elevational variations in climate warming impacts on West Himalayan fir growth - Kristina Sohar; Jan Altman; Martin Kopecký; Vít Pejcha; Samresh Rai; Pavel Fibich; Jiří Doležal (Climate Dynamics, 2024)

Changes in plant diversity of European lowland forests: Increased homogenization and expansion of shade-tolerant trees - Vojtěch Lanta; Adéla Wiatzková; Jan Altman; Michael Bartoš; Tomáš Černý; Zuzana Chlumská; Miroslav Dvorský; David Hauck; Jiří Hummel; Petr Karlík; Kenz Samraoui; Lukáš Čížek; et al. (Biological Conservation, 2024)

Revealing legacy effects of extreme droughts on tree growth of oaks across the Northern Hemisphere - Arun K. Bose; Jiri Doležal; Daniel Scherrer; Jan Altman; Daniel Ziche; Elisabet Martínez-Sancho; Christof Bigler; Andreas Bolte; Michele Colangelo; Isabel Dorado-Liñán; Igor Drobyshev; Sophia Etzold; et al. (Science of The Total Environment, 2024)

Global warming alters Himalayan alpine shrub growth dynamics and climate sensitivity - Dinesh Thakur; Jan Altman; Veronika Jandová; Pavel Fibich; Zuzana Münzbergová; Jiří Doležal (Science of The Total Environment, 2024)

Global pattern of forest disturbances and its shift under climate change - Jan Altman; Pavel Fibich; Volodymyr Trotsiuk; Nela Altmanova (Science of The Total Environment, 2024)

Global warming alters Himalayan hemlock’s climate sensitivity and growth dynamics - Samresh Rai; Jan Altman; Martin Kopecký; Vít Pejcha; Miroslav Svoboda; Jiří Doležal (Climate Dynamics, 2024)

Major tree species of Central European forests differ in their proportion of positive, negative, and nonstationary growth trends - Jakub Kašpar; Jan Tumajer; Jan Altman; Nela Altmanová; Vojtěch Čada; Tomáš Čihák; Jiří Doležal; Pavel Fibich; Pavel Janda; Ryszard Kaczka; Tomáš Kolář; Jiří Lehejček; et al. (Global Change Biology, 2024)
Temperate forests are undergoing significant transformations due to the influence of climate change, including varying responses of different tree species to increasing temperature and drought severity. To comprehensively understand the full range of growth responses, representative datasets spanning extensive site and climatic gradients are essential. This study utilizes tree‐ring data from 550 sites from the temperate forests of Czechia to assess growth trends of six dominant Central European tree species (European beech, Norway spruce, Scots pine, silver fir, sessile and pedunculate oak) over 1990–2014. By modeling mean growth series for each species and site, and employing principal component analysis, we identified the predominant growth trends. Over the study period, linear growth trends were evident across most sites (56% increasing, 32% decreasing, and 10% neutral). The proportion of sites with stationary positive trends increased from low toward high elevations, whereas the opposite was true for the stationary negative trends. Notably, within the middle range of their distribution (between 500 and 700 m a.s.l.), Norway spruce and European beech exhibited a mix of positive and negative growth trends. While Scots pine growth trends showed no clear elevation‐based pattern, silver fir and oaks displayed consistent positive growth trends regardless of site elevation, indicating resilience to the ongoing warming. We demonstrate divergent growth trajectories across space and among species. These findings are particularly important as recent warming has triggered a gradual shift in the elevation range of optimal growth conditions for most tree species and has also led to a decoupling of growth trends between lowlands and mountain areas. As a result, further future shifts in the elevation range and changes in species diversity of European temperate forests can be expected.

Linkage between growth phenology and climate-growth responses along landscape gradients in boreal forests - Jan Tumajer; Jan Altman; Jiří Lehejček (Science of The Total Environment, 2023)

Contrasting impacts of climate warming on Himalayan Hemlock growth: Seasonal and elevational variations - Samresh Rai; Jan Altman; Martin Kopecký; Kristina Sohar; Pavel Fibich; Vít Pejcha; Jiří Doležal (Dendrochronologia, 2023)

Poleward migration of tropical cyclones induced severe disturbance of boreal forest above 50° - Kirill Korznikov; Dmitriy Kislov; Jiří Doležal; Jan Altman (Science of The Total Environment, 2023)

Long-term tropical cyclones activity shapes forest structure and reduces tree species diversity of U.S. temperate forests - Pavel Fibich; Bryan A. Black; Jiří Doležal; Grant L. Harley; Justin T. Maxwell; Jan Altman (Science of The Total Environment, 2023)

Traits of dominant plant species drive normalized difference vegetation index in grasslands globally - Thore Engel; Helge Bruelheide; Daniela Hoss; Francesco M. Sabatini; Jan Altman; Mohammed A. S. Arfin‐Khan; Erwin Bergmeier; Tomáš Černý; Milan Chytrý; Matteo Dainese; Jürgen Dengler; Jiri Dolezal; et al. (Global Ecology and Biogeography, 2023)
Aim Theoretical, experimental and observational studies have shown that biodiversity–ecosystem functioning (BEF) relationships are influenced by functional community structure through two mutually non‐exclusive mechanisms: (1) the dominance effect (which relates to the traits of the dominant species); and (2) the niche partitioning effect [which relates to functional diversity (FD)]. Although both mechanisms have been studied in plant communities and experiments at small spatial extents, it remains unclear whether evidence from small‐extent case studies translates into a generalizable macroecological pattern. Here, we evaluate dominance and niche partitioning effects simultaneously in grassland systems world‐wide. Location Two thousand nine hundred and forty‐one grassland plots globally. Time period 2000–2014. Major taxa studied Vascular plants. Methods We obtained plot‐based data on functional community structure from the global vegetation plot database “sPlot”, which combines species composition with plant trait data from the “TRY” database. We used data on the community‐weighted mean (CWM) and FD for 18 ecologically relevant plant traits. As an indicator of primary productivity, we extracted the satellite‐derived normalized difference vegetation index (NDVI) from MODIS. Using generalized additive models and deviation partitioning, we estimated the contributions of trait CWM and FD to the variation in annual maximum NDVI, while controlling for climatic variables and spatial structure. Results Grassland communities dominated by relatively tall species with acquisitive traits had higher NDVI values, suggesting the prevalence of dominance effects for BEF relationships. We found no support for niche partitioning for the functional traits analysed, because NDVI remained unaffected by FD. Most of the predictive power of traits was shared by climatic predictors and spatial coordinates. This highlights the importance of community assembly processes for BEF relationships in natural communities. Main conclusions Our analysis provides empirical evidence that plant functional community structure and global patterns in primary productivity are linked through the resource economics and size traits of the dominant species. This is an important test of the hypotheses underlying BEF relationships at the global scale.

Contrasting Patterns of Soil Chemistry and Vegetation Cover Determine Diversity Changes of Soil Phototrophs Along an Afrotropical Elevation Gradient - Klára Řeháková; Kateřina Čapková; Jan Altman; Martin Dančák; Ľuboš Majeský; Jiří Doležal (Ecosystems, 2022)

Determinants of invasion by single versus multiple plant species in temperate lowland forests - Vojtěch Lanta; Pierre Liancourt; Jan Altman; Tomáš Černý; Miroslav Dvorský; Pavel Fibich; Lars Götzenberger; Ondřej Hornych; Jan Miklín; Petr Petřík; Petr Pyšek; Lukáš Čížek; et al. (Biological Invasions, 2022)

Fire, climate and biotic interactions shape diversity patterns along an Afrotropical elevation gradient - Jiří Doležal; Martin Dančák; Jan Kučera; Luboš Majeský; Jan Altman; Klára Řeháková; Kateřina Čapková; Jan Vondrák; Pavel Fibich; Pierre Liancourt (Journal of Biogeography, 2022)
Aim Untangling multiple drivers influencing biodiversity along elevation gradients is necessary for predicting the consequences of climate change on mountain communities. We examine the direct and indirect effects of macroclimate, edaphic conditions, fire frequency and putative biotic interactions on species richness and abundance of co‐occurring primary producers on Mount Cameroon. Location Mount Cameroon, Cameroon. Taxon: vascular plants, bryophytes and lichens, and soil microbial phototrophs. Methods We combine ground‐level survey of multi‐taxa diversity, soil nutrient stoichiometry, continuous climate monitoring using dataloggers and remote sensing data, for 115 plots sampled along a 2200–4000 m elevation gradient. We used GAMs to assess elevational patterns in ecosystem properties and SEMs to determine their direct and indirect effects on species richness and abundance. Results Vascular plant diversity peaked at mid‐elevation and emerged from the combined effects of intermediate levels of energy, total above‐ground standing biomass, fire frequency, guild abundances and edaphic conditions. Bryophyte–lichen diversity increased monotonically towards high elevation with decreasing temperature and increasing nutrient scarcity, while the diversity of soil phototrophs peaked at both lower elevation fire‐prone Afromontane and cold higher elevation Afroalpine zones. The role of macroclimate was indirect and scale dependent. Higher temperatures increased plant richness mainly indirectly via enhanced fire frequency, while soil N:P ratio had direct positive effect on plant richness. Precipitation decreased plant richness indirectly via decreased fire frequency. Fires also increased plant and bryophyte–lichen cover. Positive bryophyte–lichen and vascular plants associations strengthened in the Afroalpine zone. Main conclusions We demonstrate the role of disturbance/fire and biotic interactions in mitigating macroclimate effects and in controlling variation in community diversity along elevation gradients. While the macroclimate is often a strong predictor of ecological patterns along elevation gradients, our study illustrates that attributing these patterns exclusively to climate can lead to an incorrect assessment of the impact of climate change on biodiversity.

Distance decay 2.0 – A global synthesis of taxonomic and functional turnover in ecological communities - Caio Graco‐Roza; Sonja Aarnio; Nerea Abrego; Alicia T. R. Acosta; Janne Alahuhta; Jan Altman; Claudia Angiolini; Jukka Aroviita; Fabio Attorre; Lars Baastrup‐Spohr; José J. Barrera‐Alba; Jonathan Belmaker; et al. (Global Ecology and Biogeography, 2022)
Aim Understanding the variation in community composition and species abundances (i.e., β‐diversity) is at the heart of community ecology. A common approach to examine β‐diversity is to evaluate directional variation in community composition by measuring the decay in the similarity among pairs of communities along spatial or environmental distance. We provide the first global synthesis of taxonomic and functional distance decay along spatial and environmental distance by analysing 148 datasets comprising different types of organisms and environments. Location Global. Time period 1990 to present. Major taxa studied From diatoms to mammals. Method We measured the strength of the decay using ranked Mantel tests (Mantel r ) and the rate of distance decay as the slope of an exponential fit using generalized linear models. We used null models to test whether functional similarity decays faster or slower than expected given the taxonomic decay along the spatial and environmental distance. We also unveiled the factors driving the rate of decay across the datasets, including latitude, spatial extent, realm and organismal features. Results Taxonomic distance decay was stronger than functional distance decay along both spatial and environmental distance. Functional distance decay was random given the taxonomic distance decay. The rate of taxonomic and functional spatial distance decay was fastest in the datasets from mid‐latitudes. Overall, datasets covering larger spatial extents showed a lower rate of decay along spatial distance but a higher rate of decay along environmental distance. Marine ecosystems had the slowest rate of decay along environmental distances. Main conclusions In general, taxonomic distance decay is a useful tool for biogeographical research because it reflects dispersal‐related factors in addition to species responses to climatic and environmental variables. Moreover, functional distance decay might be a cost‐effective option for investigating community changes in heterogeneous environments.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Growing faster, longer or both? Modelling plastic response of Juniperus communis growth phenology to climate change - Jan Tumajer; Allan Buras; J. Julio Camarero; Marco Carrer; Rohan Shetti; Martin Wilmking; Jan Altman; Gabriel Sangüesa‐Barreda; Jiří Lehejček (Global Ecology and Biogeography, 2021)
Aim Plant growth and phenology respond plastically to changing climatic conditions in both space and time. Species‐specific levels of growth plasticity determine biogeographical patterns and the adaptive capacity of species to climate change. However, a direct assessment of spatial and temporal variability in radial growth dynamics is complicated, because long records of cambial phenology do not exist. Location Sixteen sites across European distribution margins of Juniperus communis L. (the Mediterranean, the Arctic, the Alps and the Urals). Time period 1940–2016. Major taxa studied Juniperus communis . Methods We applied the Vaganov–Shashkin process‐based model of wood formation to estimate trends in growing season duration and growth kinetics since 1940. We assumed that J. communis would exhibit spatially and temporally variable growth patterns reflecting local climatic conditions. Results Our simulations indicate regional differences in growth dynamics and plastic responses to climate warming. The mean growing season duration is the longest at Mediterranean sites and, recently, there has been a significant trend towards its extension of up to 0.44 days/year. However, this stimulating effect of a longer growing season is counteracted by declining summer growth rates caused by amplified drought stress. Consequently, overall trends in simulated ring widths are marginal in the Mediterranean. In contrast, durations of growing seasons in the Arctic show lower and mostly non‐significant trends. However, spring and summer growth rates follow increasing temperatures, leading to a growth increase of up to 0.32 %/year. Main conclusions This study highlights the plasticity in growth phenology of widely distributed shrubs to climate warming: an earlier onset of cambial activity that offsets the negative effects of summer droughts in the Mediterranean and, conversely, an intensification of growth rates during the short growing seasons in the Arctic. Such plastic growth responsiveness allows woody plants to adapt to the local pace of climate change.

Tree canopy accession strategy changes along the latitudinal gradient of temperate Northeast Asia - Pavel Janda; Olga N. Ukhvatkina; Anna S. Vozmishcheva; Alexander M. Omelko; Jiří Doležal; Pavel V. Krestov; Alexander A. Zhmerenetsky; Jong‐Suk Song; Jan Altman (Global Ecology and Biogeography, 2021)
Aim Understanding how natural forest disturbances control tree regeneration is key to predicting the consequences of globally accelerating forest diebacks on carbon stocks and forest biodiversity. Tropical cyclones (TCs) are important drivers of forest dynamics in Eastern Asia, and it is predicted that their importance will increase. However, little is known about the impact of TCs on forest regeneration. Location Latitudinal gradient from south Korea (33° N) to the Russian Far East (45° N). Time period Last 300 years. Major taxa studied Quercus mongolica , Abies nephrolepis and Pinus koraiensis . Methods We explored the effects of TC activity on canopy accession strategies derived from long‐term tree radial growth patterns along a 1,500‐km latitudinal gradient of decreasing TC activity. We analysed canopy accession strategies for > 800 trees of three widely distributed tree species by dividing them into gap trees (GTs), which established immediately after gap formation, and released trees (RTs), which accessed the upper canopy after a period of competitive suppression. Results We found a substantial decrease in GTs and increase in RTs proportionally along the gradient of decreasing TC activity. Pinus koraiensis and A. nephrolepis exhibited high variability in the proportions of the individual canopy accession strategies along the latitudinal gradient, whereas it was more stable for Q. mongolica . We identified the gradient of TC activity as the main driver influencing canopy dynamics and thus changes in life‐history traits for P. koraiensis and Q. mongolica , whereas maximal growth rate was the main driver for A. nephrolepis . Main conclusions Flexibility in growth strategies enabled the studied species to cover extensive areas and indicates that they will be able to cope with shifts in disturbance regimes induced by the poleward migration of TCs and increasing TC intensity. Our results highlight the canopy accession strategy as an ecological indicator of past disturbance activity.

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

Tree growth response to recent warming of two endemic species in Northeast Asia - Jan Altman; Kerstin Treydte; Vit Pejcha; Tomas Cerny; Petr Petrik; Miroslav Srutek; Jong-Suk Song; Valerie Trouet; Jiri Dolezal (Climatic Change, 2020)

Seasonal shifts of biodiversity patterns and species’ elevation ranges of butterflies and moths along a complete rainforest elevational gradient on Mount Cameroon - Vincent Maicher; Szabolcs Sáfián; Mercy Murkwe; Sylvain Delabye; Łukasz Przybyłowicz; Pavel Potocký; Ishmeal N. Kobe; Štěpán Janeček; Jan E. J. Mertens; Eric B. Fokam; Tomasz Pyrcz; Jiří Doležal; et al. (Journal of Biogeography, 2020)
Aim Temporal dynamics of biodiversity along tropical elevational gradients are unknown. We studied seasonal changes of Lepidoptera biodiversity along the only complete forest elevational gradient in the Afrotropics. We focused on shifts of species richness patterns, seasonal turnover of communities and seasonal shifts of species’ elevational ranges, the latter often serving as an indicator of the global change effects on mountain ecosystems. Location Mount Cameroon, Cameroon. Taxon Butterflies and moths (Lepidoptera). Methods We quantitatively sampled nine groups of Lepidoptera by bait‐trapping (16,800 trap‐days) and light‐catching (126 nights) at seven elevations evenly distributed along the elevational gradient from sea level (30 m a.s.l.) to timberline (2,200 m a.s.l.). Sampling was repeated in three seasons. Results Altogether, 42,936 specimens of 1,099 species were recorded. A mid‐elevation peak of species richness was detected for all groups but Eupterotidae. This peak shifted seasonally for five groups, most of them ascending during the dry season. Seasonal shifts of species’ elevational ranges were mostly responsible for these diversity pattern shifts along elevation: we found general upward shifts in fruit‐feeding butterflies, fruit‐feeding moths and Lymantriinae from beginning to end of the dry season. Contrarily, Arctiinae shifted upwards during the wet season. The average seasonal shifts of elevational ranges often exceeded 100 m and were even several times higher for numerous species. Main conclusions We report seasonal uphill and downhill shifts of several lepidopteran groups. The reported shifts can be driven by both delay in weather seasonality and shifts in resource availability, causing phenological delay of adult hatching and/or adult migrations. Such shifts may lead to misinterpretations of diversity patterns along elevation if seasonality is ignored. More importantly, considering the surprising extent of seasonal elevational shifts of species, we encourage taking account of such natural temporal dynamics while investigating the global climate change impact on communities of Lepidoptera in tropical mountains.

Forest structure determines spatial changes in avian communities along an elevational gradient in tropical Africa - David Hořák; Michal Ferenc; Ondřej Sedláček; Francis Njie Motombi; Miroslav Svoboda; Jan Altman; Tomáš Albrecht; Eric Djomo Nana; Štěpán Janeček; Martin Dančák; Ľuboš Majeský; Elias Ndive Lltonga; et al. (Journal of Biogeography, 2019)
Aim To test if tree species richness and forest structure drive spatial variation in avian communities along a tropical elevation gradient and to present information about the role of detailed forest parameters. Location A 2,000‐m long elevational gradient of tropical forest on Mt. Cameroon, west‐central Africa. Taxon Birds and trees. Methods We performed bird censuses and vegetation mapping at the same plots across six forested sites at elevations of 350, 650, 1,100, 1,500, 1,850, and 2,200 m a.s.l., with 16 plots per elevation. We tested the effects of elevation, forest structure and tree diversity on the species richness, functional diversity and β‐diversity of birds (Bray–Curtis dissimilarity). We used conditional inference trees based on random forests (RF) to investigate these relationships across all elevation sites as well as within elevations. Results Both tree and bird species richness declined monotonically with elevation. Vegetation structure correlated with elevation, and all vegetation attributes significantly differed among elevations. The RF explained 70% of the variance in avian species richness, with the most important predictors being elevation, proportion of dead trees, tree species richness and herb layer coverage. We found that elevation (and shrub layer) was a particularly important predictor of avian functional diversity. We identified no important predictor of bird species richness after standardization within elevations, and the proportion of dead trees was the sole important predictor of functional diversity. Within‐elevation β‐diversity in avian community composition was determined by the dissimilarity of the tree community and differences in leaf area index, solar radiation and spatial distance. The functional dissimilarity was best explained by leaf area index. Main conclusions Apart from elevation itself, spatial distance even within elevations correlated with compositional and functional variation among avian assemblages. Forest structural traits can have a significant influence on distribution of birds. Thus, gaps in the spatial distribution of species such as along elevations might be caused by fine‐scale recognition of suitable habitats.

Growth–climate relationships of Himalayan conifers along elevational and latitudinal gradients - Kristina Sohar; Jan Altman; Eliška Lehečková; Jiří Doležal (International Journal of Climatology, 2017)
High mountains are some of the most vulnerable regions to climate change and therefore a matter of global concern. Here, the climatic growth factors of conifers and their course in time and space along an elevational gradient in the northwestern Himalayan part of India were studied. Increment cores of Juniperus semiglobosa and Cedrus deodara (xeric species), and Abies pindrow and Picea smithiana (mesic species) were collected from thirteen sites. Tree‐ring width and maximum latewood density were measured and cross‐dated. The time‐series were standardized and site‐ and species‐level chronologies were built. Static and moving bootstrap correlation and response functions between the tree‐ring chronologies and monthly climatic variables were computed. The largest climate changes in the region were increasing winter and early‐spring temperatures and decreasing monsoon precipitation. The growth of all species was negatively correlated with pre‐monsoon temperature, as the higher temperatures probably increased evapotranspiration and caused water deficit. The phenomenon was most pronounced in May, but also in June for the Juniperus at the northernmost, highest, and driest sites. The pre‐monsoon temperature signal of the drought‐prone Juniperus and Cedrus endured, while the signal of the climate‐susceptible Abies and Picea at the mesic sites was unstable. Namely, the May temperature signal of Picea became significant since the second half of the last century whereas the signal of Abies shifted from May to April. This apparently related to the earlier onset of spring due to the accelerated warming in the region. Besides, maximum latewood density of Picea and Abies negatively correlated with May and June temperature, respectively. Additionally, the Cedrus benefitted from winter precipitation and the Abies and Picea from pre‐monsoon rainfall. Counterintuitively, we detected no direct effect of monsoon precipitation decrease on the conifers because their growth was driven by pre‐monsoon conditions, which changed only slightly.

Annual and intra-annual growth dynamics of Myricaria elegans shrubs in arid Himalaya - Jiri Dolezal; Eliska Leheckova; Kristina Sohar; Miroslav Dvorsky; Martin Kopecky; Zuzana Chlumska; Jan Wild; Jan Altman (Trees, 2016)

Linking two centuries of tree growth and glacier dynamics with climate changes in Kamchatka - Jiri Dolezal; Jan Altman; Valentina P. Vetrova; Toshihiko Hara (Climatic Change, 2014)

Forest response to increasing typhoon activity on the K orean peninsula: evidence from oak tree‐rings - Jan Altman; Jiří Doležal; Tomáš Černý; Jong‐Suk Song (Global Change Biology, 2013)
The globally observed trend of changing intensity of tropical cyclones over the past few decades emphasizes the need for a better understanding of the effects of such disturbance events in natural and inhabited areas. On the K orean P eninsula, typhoon intensity has increased over the past 100 years as evidenced by instrumental data recorded from 1904 until present. We examined how the increase in three weather characteristics (maximum hourly and daily precipitation, and maximum wind speed) during the typhoon activity affected old‐growth oak forests. Q uercus mongolica is a dominant species in the K orean mountains and the growth releases from 220 individuals from three sites along a latitudinal gradient (33–38°N) of decreasing typhoon activity were studied. Growth releases indicate tree‐stand disturbance and improved light conditions for surviving trees. The trends in release events corresponded to spatiotemporal gradients in maximum wind speed and precipitation. A high positive correlation was found between the maximum values of typhoon characteristics and the proportion of trees showing release. A higher proportion of disturbed trees was found in the middle and southern parts of the K orean peninsula where typhoons are most intense. This shows that the releases are associated with typhoons and also indicates the differential impact of typhoons on the forests. Finally, we present a record of the changing proportion of trees showing release based on tree‐rings for the period 1770–1979. The reconstruction revealed no trend during the period 1770–1879, while the rate of forest disturbances increased rapidly from 1880 to 1979. Our results suggest that if typhoon intensity rises, as is projected by some climatic models, the number of forest disturbance events will increase thus altering the disturbance regime and ecosystem processes.